Students’ perception on the implementation of Project-Based Learning in Writing Instruction at SMA Bala Keselamatan Palu - Day, Jein Silsilia; Kamaruddin, Abdul; Lebagi, Desrin; Nadrun, Nadrun (Universitas Pahlawan Tuanku Tambusai, 2025)
Project-Based Learning (PjBL) is one of the learning methods in the independent curriculum and is a proven effective teaching methods in writing. However, few studies have explored students' perceptions of the implementation of PjBL in writing. Therefore, this study investigates students' perceptions of the level of participation, benefits, and challenges in the implementation of PjBL in writing instruction among tenth-grade students at SMA Bala Keselamatan Palu. This study selected 7 students through purposive sampling, and data were obtained through semi-structured interviews and focus group discussions in a qualitative phenomenological design. The results showed that they were actively involved in the learning process and increased their confidence in writing, even though they also faced various challenges, including limited vocabulary and differences of opinion within the group. However, most students generally had positive perceptions. In conclusion, PjBL is considered an effective teaching method in writing instruction.